Optimizing sexual and reproductive health across the lifespan in people with cystic fibrosis. (8th October 2021) - West, Natalie E.; Kazmerski, Traci M.; Taylor‐Cousar, Jennifer L.; Tangpricha, Vin; Pearson, Kelsie; Aitken, Moira L.; Jain, Raksha
Abstract: With improved therapies, people with cystic fibrosis are living longer and healthier lives and increasingly have questions surrounding their sexual and reproductive health. This article will summarize the important issues of which providers should be aware during the lifespan of people with cystic fibrosis, including puberty, adulthood, and menopause. A wide range of sexual and reproductive health topics are addressed such as puberty, transgender and gender nonbinary identities, contraception, sexually transmitted infections, hypogonadism, sexual functioning, cyclical hemoptysis, and urinary incontinence. We discuss gaps in knowledge and current evidence as well as management strategies to optimize care. Our goal is to support providers to enable them to give comprehensive care throughout the lifespan of people with cystic fibrosis.